Investigating Knowledge, Attitude and Practices of Under Graduate Students Regarding Obesity, in Peshawar, Pakistan - Zia Ul Ain Sabiha, Ghazal Rasool, Tayyaba Zia, Inam-U-Llah, Rehana Rasool, Ubaidullah, Sudhair Abbas Bangash, Mahnoor8, Nimra, Irfan Ullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Throughout all countries, obesity and overweight are the most significant health issues, and they are becoming more and more common. Numerous studies have demonstrated the link of obesity with a wide variety of illnesses, including hyperlipidemia, type 2 diabetes, coronary heart disease, hypertension and breast cancer. In 1300 pupils, this study sought to know about the knowledge, attitude and practices (KAP) of obesity. Methods: In order to conduct a cross-sectional study, measurements of waist circumference, height, hip circumference and weight were taken. FFQ, or 24-hour dietary survey, was completed. In order to evaluate obesity and overweight, BMI were utilized. Data was examined using SPSS 19's statistical tool. Results: The average age of students was 21.5 +/- 2.2, with 850 (65.38%) of all pupils being female. According to BMI, 429 pupils (33%) and 52 pupils (04%) are overweight and obese respectively. Among these overweight and obese students 228 and 42 (53%& 81%) were female respectively. Conclusions: Overweight and obesity rates were substantially higher in female students than in male. The intermediate to high frequency of overweight and obesity among students at Pakistani Institute highlights the significance of over eating, lack of physical activities and substantially little knowledge about dieting and balance diet. Keywords: Obesity, body mass index, Pakistan